2019
DOI: 10.1371/journal.pone.0218020
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with neonatal hypothermia on admission to neonatal intensive care units in Southwest Ethiopia – A cross-sectional study

Abstract: Introduction Neonatal hypothermia is one of the main underlying factors associated with neonatal deaths. Objective The objective of this study was to assess the prevalence and factors associated with neonatal hypothermia on admission to neonatal intensive care units in Southwest Ethiopia. Methods Institution-based cross-sectional study design was employed between February to September 2017 at intensive care units of Arba Minch and Jinka Gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 21 publications
1
37
0
Order By: Relevance
“…1, Table S2, and Table S3). Table 1 summarizes the characteristics of the 12 included studies in this systematic review [10,14,18,[22][23][24][25][26][27][28][29][30] Eight studies were found in Ethiopia [10,18,[23][24][25][26][27][28], 2 in Kenya [29,30], while 2 were from Uganda [14,22]. Nine studies were cross-sectional, while the others used either casecontrol (n = 1) or cohort (n = 2) study design.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1, Table S2, and Table S3). Table 1 summarizes the characteristics of the 12 included studies in this systematic review [10,14,18,[22][23][24][25][26][27][28][29][30] Eight studies were found in Ethiopia [10,18,[23][24][25][26][27][28], 2 in Kenya [29,30], while 2 were from Uganda [14,22]. Nine studies were cross-sectional, while the others used either casecontrol (n = 1) or cohort (n = 2) study design.…”
Section: Resultsmentioning
confidence: 99%
“…Timely initiation of breastfeeding is considered as initiating breastfeeding within 1 hour after birth. Five studies found a significant association between delayed initiation of breastfeeding and neonatal hypothermia [10,[25][26][27][28]. The odd of neonatal hypothermia among newborns with delayed initiation of breastfeeding range from 1.63 [28] to 4.39 [10] (Table 3).…”
Section: Factors Associated With Neonatal Hypothermia In Eastern Afrimentioning
confidence: 99%
See 2 more Smart Citations
“…To reduce the rates of these complications, many clinical studies have suggested various measures to prevent hypothermia, including plastic wrapping without drying [12,13,14], the use of incubators [15], and the use of chemical mattresses [16]. Despite [10,17].…”
Section: Introductionmentioning
confidence: 99%